The effectiveness of MOOCs in ESP for technical students: A Kazakhstan case study - Akhmetova, D.R.; Kopzhasarova, U.I.; DeVereaux, C. (XLinguae, 2023)
This study looks at the critical problem of how to use Massive Open Online Courses (MOOCs) at the Republic of Kazakhstan’s technical universities. Its objective is to study how professional-oriented foreign languages can be taught as MOOCs. As a methodological basis, it uses system-activity and competence approaches. The theoretical side includes the analysis and generalization of foreign and local scientific works to determine the advantages and disadvantages of MOOCs in the development of professional foreign language skills for students with technical specialties. Data on the use of MOOCs was analyzed and summarized at Karaganda Technical University. The quantitative results of the experiment were obtained using mathematical statistics. The authors ran a comparative analysis of the results between groups with traditional and mixed teaching methods in the English for Special Purposes course. A mixed method with MOOC technology integrated delivers better results than traditional education. Empirical results demonstrate that this method improves communication skills in the main areas of speech activity, professional vocabulary expansion, and theoretical knowledge enrichment of students within their specialty. The results indicate that using MOOCs as part of the ESP course leads to better educational results in comparison to traditional education. The use of system-activity and communicative approaches unlocked new opportunities for students, like increasing English proficiency levels, developing critical thinking and time-management skills, solving problems, and advancing their knowledge of their discipline. The authors studied MOOCs in a small data environment using an alternative qualitative research analysis method and came to the conclusion that MOOCs are effective in ESP courses for engineering students.
Keywords: innovative information technology; Massive Open Online Courses (MOOC); professional-oriented foreign language; blended learning methods; National Open Education Platform; Small Private Online Course (SPOC); English for Special Purposes (ESP)